Suppressing the ions-induced degradation for operationally stable perovskite solar cells. (October 2019) - Li, Xiaodong; Fu, Sheng; Liu, Shiyu; Wu, Yulei; Zhang, Wenxiao; Song, Weijie; Fang, Junfeng
Abstract: Operational stability remains the foremost concern delaying the commercialization of perovskite solar cells (PSCs). Ions diffusion from iodine-rich perovskite layer to metal electrode is one main reason for the irreversible devices degradation. Here we introduce chemically crosslinked TMTA (trimethylolpropane triacrylate) at both bulk perovskite layer and perovskite/PCBM interface to suppress the ions diffusion toward electrode. The TMTA in perovskite layer suppresses ions migration along grain boundaries and TMTA at perovskite/PCBM interface blocks ions diffusion toward electrode, owing to its continuous network structure and chemically inert nature. Diffusion experiment, permeation experiment and resistive random-access memory (RRAM) investigation confirm the effectively blocked ions diffusion in PSCs with TMTA whether under heat, light or electric field conditions. The resulting PSCs exhibit 7-fold improvement in operational stability at elevated temperature of 60 °C, retaining ~80% of initial efficiency after maximum power point tracking for 1000 h under continuous illumination. The PSCs with TMTA also exhibit good thermal stability and retain over 90% of the initial efficiency after aging at 60 °C for 1000 h. Graphical abstract: Operationally stable perovskite solar cells (PSCs) are fabricated through introducing chemically crosslinked TMTA (trimethylolpropane triacrylate) at both bulk perovskite layer and perovskite/PCBM interface. TMTA in perovskite layer suppresses ions migration along grain boundaries and TMTA at perovskite/PCBM interface blocks ions diffusion toward electrode. The ions diffusion in PSCs is effectively suppressed whether under heat, light or electric field conditions. The resulting PSCs retain ~80% of initial efficiency after MPP tracking at 60 °C for 1000 h.Image 1 Highlights: Ions blocking strategy is proposed to fabricate operational stable perovskite solar cells (PSCs). TMTA is introduced in both perovskite layer and perovskite/PCBM interface to suppress ions-induced degradation. PSCs exhibit good operational stability, retaining ~80% of initial efficiency after MPP tracking for 1000 hours at 60°C.